PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2018)
This study aims to analyze empirical evidence of the effect of service quality on customer satisfaction and its impact on customer loyalty at PT Indovisual Service Solution Jakarta. Samples in this study were 124 customers, probability sampling techniques, namely sampling techniques that provide equal opportunities for each element (member) of the population to be selected as sample members. Analysis of the data used is Structural Equation Modeling (SEM). empirical research results Service quality has a positive and significant effect on customer satisfaction. These results indicate that by improving the quality of service, customers will feel satisfied with the services provided. Service Quality has a positive and significant effect on customer loyalty. These results indicate that by improving the quality of service, customers will feel loyal and will continue to use the services of PT Indovisual Service Solution. Customer satisfaction does not have a significant positive effect on customer loyalty. This means that the lower the customer satisfaction, customer loyalty will also decrease the quality of service has a positive and significant effect on customer loyalty. These results indicate that by improving the quality of service, customers will feel loyal and will continue to use the services of PT Indovisual Service Solution